Gait stability in peripheral artery disease: a phase-dependent analysis using gait tube methodology - Mohammadzadeh Gonabadi, Arash; Pipinos, Iraklis I.; Myers, Sara A.; Fallahtafti, Farahnaz (Frontiers in Rehabilitation Sciences, 2026)
IntroductionPeripheral Artery Disease (PAD) affects over eight million U.S. adults, impairing mobility, quality of life, and increasing fall and cardiovascular risks. PAD reduces lower limb blood flow and contributes to neuromuscular dysfunction, leading to unstable gait. Traditional stability metrics often miss phase-specific changes. Gait Tube Stability (GTS) is a phase-dependent, three-dimensional method that analyzes center of mass (COM) velocity using ellipsoidal variability to detect directional instability. This study examined whether GTS can identify phase-specific gait deficits in PAD compared with age-matched controls.MethodsFifty-two PAD patients and 132 healthy individuals walked on a force-instrumented treadmill at self-selected speeds. GTS metrics-including ellipsoid volume and direction-specific variabilities (AP, ML, VT)-were computed from 3D COM velocity. Data were segmented by gait phase and analyzed using Wilcoxon rank-sum tests and Statistical Parametric Mapping (SPM).ResultsPAD patients exhibited significantly lower ellipsoid volumes (3.07 × 105 mm³/s³, p < 0.001) and reduced VT variability (40.29 mm/s, p < 0.001) compared to controls (1.02 × 106 mm³/s³ and 93.60 mm/s). No significant differences were found in AP (p = 0.1062) or ML (p = 0.6467) variability. Correlation between ellipsoid volume and total variability was weak in PAD (r = 0.06, p = 0.6587) but moderate in controls (r = 0.55, p < 0.001), indicating impaired multidirectional coordination in PAD. Correlation analysis revealed a significant association between ellipsoid volume and total variability in controls but not in PAD, and Fisher's r-to-z test confirmed a significant between-group difference (p = 0.005).DiscussionGTS revealed phase-specific gait deficits in PAD, especially during weight acceptance and early stance, indicating a constrained, energy-conserving strategy that may elevate fall risk. By detecting critical instability phases, GTS can guide targeted physical therapy, assistive device use, and optimal timing for robotic or exoskeleton support-supporting personalized interventions and offering a sensitive tool for clinical gait stability assessment.